The efficiency of healthcare system expenditures: Evidence from Croatia - Sabina Hodžić; Dijana Vuković; Adis Muharemović (Ekonomski Vjesnik, 2019)
Offering an efficient healthcare system is one of the main focuses of economic development for every country in the world, including Croatia, in order to achieve a better quality of life and healthcare protection. As a result, there is also a higher standard of living for the citizens. The healthcare system in Croatia has undergone a number of reforms. For each of the implemented reforms, the objective was to optimize the healthcare system in line with the government’s budget to achieve sustainability in the long run. Therefore, the healthcare financing system and sustainability play an important role. The objective of this paper is to evaluate and analyze the efficiency of average healthcare expenditures in twenty Croatian counties by applying the data envelopment analysis approach. The analysis was conducted for the 2010-2017 period. To assess the performance of the counties, we used three inputs and three outputs. The results revealed significant differences in the efficiency of healthcare expenditures among the Croatian counties. Therefore, the results of scale efficiency showed that, among the twenty Croatian counties, only six counties (Brod-Posavina, Koprivnica-Križevci, Lika-Senj, Međimurje, Vukovar-Srijem and Zagreb) operate at the maximum score.